Primary health care "approach" and medical education: New opportunities for revitalizing the bond - Mohit P Gandhi (Wolters Kluwer Medknow Publications, 2020)
The importance of primary health care (PHC) has once again been reiterated in the Astana Declaration of 2018. PHC is an approach to health systems development rather than just a level of health-care service delivery. Understanding the PHC "approach" is crucial for doctors, across specializations and levels, as they are one of the prominent players in the country's health system. Undergraduate medical education offers an ideal window of opportunity to do so. The medical education policy, time and again, has acknowledged this need and has created mechanisms to fulfill it. The role of departments of community medicine has been kept central in these policy prescriptions. This, in practice, has led other departments to play only a weak role in the teaching and application of PHC. The Medical Council of India's new competency-based medical curriculum, with a renewed focus on integrated teaching, offers fresh opportunities to change this situation.